Clinical heterogeneity of hypophysitis secondary to PD-1/PD-L1 blockade: insights from four cases. (12th October 2019) - Lupi, Isabella; Brancatella, Alessandro; Cosottini, Mirco; Viola, Nicola; Lanzolla, Giulia; Sgrò, Daniele; Dalmazi, Giulia Di; Latrofa, Francesco; Caturegli, Patrizio; Marcocci, Claudio
Abstract : Summary: Programmed cell death protein 1/programmed cell death protein ligand 1 (PD-1/PD-L1) and cytotoxic T-lymphocyte antigen 4/B7 (CTLA-4/B7) pathways are key regulators in T-cell activation and tolerance. Nivolumab, pembrolizumab (PD-1 inhibitors), atezolizumab (PD-L1 inhibitor) and ipilimumab (CTLA-4 inhibitor) are monoclonal antibodies approved for treatment of several advanced cancers. Immune checkpoint inhibitors (ICIs)-related hypophysitis is described more frequently in patients treated with anti-CTLA-4; however, recent studies reported an increasing prevalence of anti-PD-1/PD-L1-induced hypophysitis which also exhibits slightly different clinical features. We report our experience on hypophysitis induced by anti-PD-1/anti-PD-L1 treatment. We present four cases, diagnosed in the past 12 months, of hypophysitis occurring in two patients receiving anti-PD-1, in one patient receiving anti-PD-1 and anti-CTLA-4 combined therapy and in one patient receiving anti-PD-L1. In this case series, timing, clinical presentation and association with other immune-related adverse events appeared to be extremely variable; central hypoadrenalism and hyponatremia were constantly detected although sellar magnetic resonance imaging did not reveal specific signs of pituitary inflammation. These differences highlight the complexity of ICI-related hypophysitis and the existence of different mechanisms of action leading to heterogeneity of clinical presentation in patients receiving immunotherapy. Learning points: PD-1/PD-L1 blockade can induce hypophysitis with a different clinical presentation when compared to CTLA-4 blockade. Diagnosis of PD-1/PD-L1 induced hypophysitis is mainly made on clinical grounds and sellar MRI does not show radiological abnormalities. Hyponatremia due to acute secondary adrenal insufficiency is often the principal sign of PD-1/PD-L1-induced hypophysitis and can be masked by other symptoms due to oncologic disease. PD-1/PD-L1-induced hypophysitis can present as an isolated manifestation of irAEs or be in association with other autoimmune diseases